EVALUASI PROFESI GURU DAN KEBIJAKAN SEKOLAH DI MADRASAH IBTIDAIYAH DARUSSALAM 1 TAMBALANG KECAMATAN SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - Nazmi Fuadi; Muhammad Yuliansyah (Bajang Institute, 2025)
This study aims to examine how school policies are implemented in teacher professional evaluation at Madrasah Ibtidaiyah Darussalam 1 Tambalang, and to identify factors that support or hinder the process. In addition, this study also explores various efforts made by schools to overcome the obstacles that arise, so that teacher professional evaluation can run more effectively and in line with established policies. The results of the study indicate that teacher professional evaluation at Madrasah Ibtidaiyah Darussalam 1 Tambalang begins with planning and establishing competency development programs, including training, courses, empowerment of MGMP (Subject Teacher Deliberation), and writing and reading activities to improve teacher professionalism. The main supporting factor is teacher motivation to carry out their profession seriously, while obstacles that arise are overcome with a mature competency development strategy, increasing insight into the field of study, and mastery of effective teaching methods to support a more optimal teaching and learning process.